Causes and Effects of Processes’ Complexity in Public Institutions: Some Experiences from Italian Universities - Guido Modugno; Ferdinando Di Carlo; Manuela Lucchese (Administrative Sciences, 2022)
This paper addresses the issue of complexity in the administrative processes in public institutions; in particular, accounting routines and processes are examined. Back-office activities, although having a merely supporting role in the delivery of public services, are often quite complex and use a significant amount of public institutions’ resources. However, the literature reveals a scarce use of accounting data by politicians and citizens. While the relation between complexity and costs has been the subject of major research in the business world, this issue is still unexplored with regard to the administrative processes of public institutions. This paper is based on an in-depth analysis of two cases in the higher education sector.